The role of Christian religious education teacher in preventing and resolving student conflicts - Lumamuly, Pitersina Christina (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
A school is a place for students to meet and learn, as well as to improve and refine their behavior to be excellent in cognitive, affective, and psychomotor. To realize this, students try to highlight all their abilities. However, slight friction appeared, which impacted individual and even group conflicts. The abuse attitude is performed in disrespectful action, mocking, unrespectful debating. They are happened both inside and outside the school. This study describes the importance of Christian Religious Education Teachers' (PAK) Role in preventing and resolving conflicts. The method used in this research was the descriptive qualitative research method. Data were collected through observation, interview, literature study. After that, they are analyzed in-depth and described descriptively. The result shows that Christian Religious Education Teachers' role as communicators is an effective way to resolve student conflict.